Review of the environmental impact assessment process of wastewater treatment plants in Spain - Fuentes-Bargues, Jose Luis (Oficyna Wydawnicza Politechniki Wrocławskiej, 2018)
The environmental impact over natural water systems, both marine and land, of the sewage is minimized with the treatment at Wastewater Treatment Plants (WWTPs), but these facilities also generate environmental impacts during the construction period and during the operation period. A review of the environmental impact assessment (EIA) process of WWTPs in Spain through the analysis of records of decision (RODs) between 2000 and 2016 has been performed in this work. The major environmental impacts during the construction period are noise, land use and disturbance of the air and water’s quality. During the operation period, the major environmental impacts are noise, odors from the depuration process and the visual impact of the facilities. About the EIA process, results show the processing time is too long, scoping phase has a success rate about 57.2% and regional public administrations are the most participative, both at scoping phase and at public participation phase. In general, public participation during period of exhibition is very low, in twelve of the RODs nobody submitted any report. The role of environmental project manager and the work environmental journal must be strengthened.
Environment Protection Engineering. Vol. 44, 2018, nr 4, s. 23-41
Keywords: ochrona środowiska; inżynieria środowiska; czasopisma